GM plants: Science, politics and EC regulations - Davison, John (Plant science (Limerick), 2010)
The EU has the probably strictest regulations in the world for the presence of GMOs in food and feed. These require the labeling of food and feed where the level of approved GMO exceeds 0.9% of unintentional adventitious presence. For non-approved GMOs the threshold is ‘zero’ and thus requires that cargoes containing GMOs non-approved GMOs are returned to the port of origin or are destroyed. The process of GMO safety approval is slow and subject to extensive political interference. However outside of Europe, new GMOs are being created, approved and cultivated at a rate exceeding that of EU approvals. Since current methods of cultivation, storage and transport do not permit complete segregation of GMO and non-GMO crops, some co-mingling must be expected. This leads to a peculiar situation where the EU is dependent on imports (particularly soybean for animal feed) from North and South America and yet, legally, must reject these imports since they contain low levels of unauthorized GMOs. Several authorative European reports indicate that this is not a sustainable situation and must result in feed shortages and price increases of meat and poultry. The solution is to either to modify EU regulations or to synchronize GMOs approvals on an international level. The USA has constantly criticized the EU for its unscientific GMO regulations which it says amounts to trade protectionism. Very recently however, the USA has realized that other countries are now producing and cultivating their own GMOs, and that these are not authorized in the USA. The USA is thus proposing to set up its own system of GMO regulations which may bear a close similarity to those in Europe.